Implementasi Shuffling Algoritma Dalam Tes Ujian Masuk Peserta Didik Baru di SMA Swasta An-Nizam - Harahap, Muhammad Soleh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The exam is one way to evaluate the learning process. In the world of exam education is intended to measure the level of achievement of a teaching goal and a learning process so that students or students and related institutions can know the level of ability in understanding the field of study that has been taken. In this study the author will try to build an online examination system in which the Fisher-Yates algorithm is applied for randomization of the questions. The system is designed to only apply the process of randomizing the test questions and the randomization process so that different questions can be issued.